Mental health of health professionals in hospital environment: Literature review on the Brazilian scenario in COVID-19 (Research, Society and Development, 2023)
The objective was to survey empirical studies published in 2020 and 2021 aimed at the mental health of health professionals working in the Brazilian hospital environment during the COVID-19 scenario. A narrative review was carried out evaluating articles in two national databases. Six articles were selected, whose data were collected between April and August 2020, in which most participants were from the nursing area. The main perceived symptoms were compatible with a diagnosis of depression and anxiety. However, there were other negative symptoms, such as stress, physical and psychological suffering, hopelessness, among others. The importance of further studies with this public during March and April 2021 is highlighted, given the increase in demand due to the high number of cases and deaths from COVID-19. In addition, longitudinal studies can be carried out to find out about the impact on the life and health of these professionals that may have been caused during this period.